Cyclodextrin-based sustained gene release systems: a supramolecular solution towards clinical applications. (11th December 2018) - Xu, Chenfang; Wu, Yun-Long; Li, Zibiao; Loh, Xian Jun
Abstract : Recent advances of using cyclodextrin (CD) based supramolecular structures as sustained gene release systems are summarized. Abstract : Recently, sustained release vectors, especially cyclodextrin (CD) based supramolecular carriers, have been reported to play an important role and have spurred interesting developments as novel gene delivery systems. This review will summarize the recent designs of CD-based supramolecular structures as sustained gene release systems in terms of CD-based graft copolymers, polyrotaxanes or polypseudorotaxanes, and supramolecular hydrogels; the advantages of these CD-based supramolecular carriers in terms of biocompatibility, gene transfection ability and controllable release rate by tuning the de-threading of CDs; and the applications of these CD-based supramolecular sustained gene release systems in disease treatments by taking advantage of their increase of the therapeutic gene's treatment period, thereby improving the gene transfection efficiency and avoiding repeated administration to increase patient compliance. Last but not least, the further endeavour towards CD-based supramolecular structures as more precise sustained gene release systems will also be discussed.